Solution Diversity and the Quality of Groups Decisions - Wanous, John P.; Youtz, Margaret A. (Academy of Management Journal, 1986)
In this article the authors discuss research they conducted that examined the relationship between solution diversity and the quality of group decision making. They note that if a positive link can be identified between the two then further research can be conducted to examine what managerial methods best stimulate diversity in solutions. The authors also wanted to examine if solution diversity was at all linked to group composition, a subject area that has been more extensively studied than their main focus. Some of their suggestions for increasing solution diversity include incorporating a devil's advocate, inviting outsiders into groups and holding second chance meetings.